"Metro Manila discos" relevance of interior designing for Metro Manila discos - Sison, Michelle D.; Florendo, Raquel Baltazar (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman
Keywords: Bars (Drinking establishments) -- Philippines -- Manila -- Interior decoration